2013
DOI: 10.1088/0960-1317/23/9/095010
|View full text |Cite
|
Sign up to set email alerts
|

An approach for controlling printed line-width in high resolution roll-to-roll gravure printing

Abstract: One of the challenges in printed electronics is the capacity to print a high resolution electrode. However, it is difficult to gain control over fidelity of microscale line-width of printed patterns especially in roll-to-roll (R2R) gravure printing process. Here, we report a simple solution based on the wettability of ink on the substrate to prevent a widening effect of printed patterns thereby enhancing the precision. The widening effect was found to be affected by intrinsic (ink wetting behavior, cell geomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 37 publications
(50 reference statements)
0
33
0
Order By: Relevance
“…Therefore, the printed layers should be defect-free, uniform and homogeneous with very controlled thicknesses [6][7][8]15]; very low roughness is also a crucial feature since the morphology of the previous printed layers can influence the properties of the successive layers [14]. In order to further improve the quality of the produced layer with the aim to prove it as anode into an OLED, increasing the printing speed was here tried without changing ink (viscosity, solvent) and other process parameters (cells geometry, nip pressure), looking for the optimal conditions of the ink transfer step [12,[15][16][17]. In Table 1 the characteristics of the printed anodes are showed and compared with the ones of the anode obtained by spin coating.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the printed layers should be defect-free, uniform and homogeneous with very controlled thicknesses [6][7][8]15]; very low roughness is also a crucial feature since the morphology of the previous printed layers can influence the properties of the successive layers [14]. In order to further improve the quality of the produced layer with the aim to prove it as anode into an OLED, increasing the printing speed was here tried without changing ink (viscosity, solvent) and other process parameters (cells geometry, nip pressure), looking for the optimal conditions of the ink transfer step [12,[15][16][17]. In Table 1 the characteristics of the printed anodes are showed and compared with the ones of the anode obtained by spin coating.…”
Section: Resultsmentioning
confidence: 99%
“…To quantitatively investigate the effect of the nip force on the ink transfer ratio, the ink transfer ratio was calculated by Eq. (12). Figs.…”
Section: Resultsmentioning
confidence: 97%
“…With line widths smaller than 20 µm due to the deformation of a blanket, a gravure printing is arguably one of the most promising techniques for building patterns at high resolutions. [8][9][10][11][12] There have been a number of studies on the use of high-resolution gravure printed electrodes for ink transfer as functions of the cell geometry, the printing speed and the viscosity of the ink. Sung concluded that ink transfer is a function of the cell configuration and the ink viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…In detail, the nip and doctoring pressure determine the filling, setting, and printing phase on the gravure cell to the substrate. The optimized value of pressure was selected by the experimental procedure followed in previous work [31,22]. After finishing the gravure printing process, the wound film was sampled by a slitting process and was laser-drilled at the interconnection point.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, studies have investigated stable and unstable regions of several parameters in R2R gravure printing. Furthermore, to minimize the printing scale and improve important process parameters, guidelines have been suggested for optimizing the R2R gravure printing process [21,22].…”
Section: Introductionmentioning
confidence: 99%